ANALISIS TINGKAT KESADARAN MASYARAKAT KECAMATAN MEDAN BARU DALAM MEMBAYAR ZAKAT - Herfita Rizki Hasanah Gurning; Haroni Doli Hamoraon Ritonga (Departemen Ekonomi Pembangunan USU, 2015)
The purpose of this research is to determine the level of people’s consciousness in paying zakat in Medan Baru.This research characteristic is descriptive. The data in this research are primary data and secondary data. The collecting of the primary data is done by giving questionnaire to muslims in Medan Baru were categorized as Muzakki. while secondary data are obtained from Badan Pusat Statistik, Mosques at Medan Baru, and other literatures. The descriptive analysis method by using computer SPSS 21.From 100 respondens that observed, obtained that the level of people’s consciousness in paying zakat fitrah in Medan Baru is higher than the level of people’s consciousness in paying zakat maal. It shown by average value for the level of people’s consciousness in paying zakat fitrah is 4,84 of 5, the level is categorized as ‘Excellent’. As for the level of people’s consciousness in paying zakat maal is 3,21 of 5, the level is categorized as ‘Good’. While, the level of people’s consciousness in paying zakat in Medan Baru is relative ‘Good’ with the value is 3,98 of 5.Keywords: The Level of Consciousness, Zakat, Zakat Mal, Zakat Fitrah.